Double Flash Illusions: Current Findings and Future Directions - Keil, Julian (Frontiers in Neuroscience, 2020)
Twenty years ago, the first report on the sound-induced double flash illusion, a visual illusion induced by sound, was published. In this paradigm, participants are presented with different numbers of auditory and visual stimuli. In case of an incongruent number of auditory and visual stimuli, the influence of auditory information on visual perception can lead to the perception of the illusion. Thus, combining two auditory stimuli with one visual stimulus can induce the perception of two visual stimuli, the so-called fission illusion. Alternatively, combining one auditory stimulus with two visual stimuli can induce the perception of one visual stimulus, the so-called fusion illusion. Overall, current research shows that the illusion is a reliable indicator of multisensory integration. It has also been replicated using different stimulus combinations, such as visual and tactile stimuli. Importantly, the robustness of the illusion allows the widespread use for assessing multisensory integration across different groups of healthy participants and clinical populations and in various task setting. This review will give an overview of the experimental evidence supporting the illusion, the current state of research concerning the influence of cognitive processes on the illusion, the neural mechanisms underlying the illusion, and future research directions. Moreover, an exemplary experimental setup will be described with different options to examine perception, alongside code to test and replicate the illusion online or in the laboratory.